Enhancement of leach protocol using combinational TSP-AI to improve the lifetime of the network - Swroop, Chandan; Wasson, Vikas (International Journal of Engineering and Technology, 2018)
Wireless sensor networks (WSNs) are come into a demand in recent years, as we seen the wide growth in the lots of wireless devices which includes cellular phones, laptops, washing machines, air-conditioner etc. WSN is a collection of tiny sensor nodes in which one node communicates with other without any physical connection and communication depends on the network lifetime. So the lifetime of WSN is a major factor and need to improve the network lifetime by using the improved routing protocol. In this paper, presents an im-proved LEACH routing protocol for WSN based on the concept of Artificial Intelligence technique with the Travelling Salesmen Prob-lems approach (TSP-AI). To minimize lifetime dissipation in the WSN, artificial neural network is used to design an improved routing protocol and discover an optimal route for the transmission of data.